Development and validation of the team perceived virtuality scale - Handke, L.; Costa, P.; Feitosa, J. (Academy of Management Annual Meeting Proceedings 2024, 2024)
With the strong proliferation of virtual teams across various organizations and contexts, understanding how virtuality affects teamwork has become fundamental to team and organizational effectiveness. However, current conceptualizations of virtuality rely almost exclusively on more or less fixed, structural features, such as the degree of technology reliance. In this paper, we take a socio-constructivist perspective on team virtuality, focusing on individuals’ experience of team virtuality, which may vary across teams and time points with similar structural features. More specifically, we develop and validate a scale that captures the construct of Team Perceived Virtuality (Handke et al., 2021). We present the results of five different studies that demonstrate the construct’s content, structural, discriminant, and criterion validity with an overall number of 2,294 teams. The final instrument comprises 10 items that measure the two dimensions of Team Perceived Virtuality (collectively-experienced distance and collectively-experienced information deficits) with five items each. This final scale showed a very good fit to a two-dimensional structure both at individual and team levels and adequate psychometric properties including aggregation indices. We further provide evidence for conceptual and empirical distinctiveness of the two TPV dimensions based on related team constructs, and for criterion validity, showing the expected significant relationships with leader-rated interaction quality and team performance. Lastly, we generalize results from student project teams to an organizational team sample.